Low-dose radiotherapy and concurrent FOLFIRI-bevacizumab: a Phase II study. (March 2016) - Morganti, Alessio Giuseppe; Cellini, Francesco; Mignogna, Samantha; Padula, Gilbert DA; Caravatta, Luciana; Deodato, Francesco; Picardi, Vincenzo; Macchia, Gabriella; Cilla, Savino; Buwenge, Milly; Lullo, Liberato DI; Gambacorta, Maria Antonietta; et al.
Aims: Low-dose radiation therapy (LDRT) can increase biological efficacy of chemotherapy. This Phase II trial evaluates LDRT plus FOLFIRI-bevacizumab (FOLFIRI-B) in metastatic colorectal cancer.Materials & methods: Primary objective: raising the clinical complete response rate from 5 to 25%. Secondary objectives: toxicity, progression-free survival. Patients underwent 12 FOLFIRI-B cycles plus two daily LDRT fractions (20 cGy/6 h interval) on each cycle. Statistical analysis was planned on 18 patients.Results: Results on 18 patients are reported. Specifically considering irradiated sites: 15/18 patients had a partial (11/18) or complete (4/18) response. Among 11 partial responders, three became a pathological CR after surgery. Grade 3–4 toxicity was recorded in two patients (11.1%). At median follow-up of 30 months (range: 8-50), 7/18 patients progressed in irradiated sites.Conclusion: Seven out of 18 patients (38.9%) had clinical or pathological CR in lesions treated with LDRT. Further studies on this newer treatment modality seem justified.